2022
DOI: 10.1021/acsaem.2c00304
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Passivation Strategy of Cationic and Anionic Defects for Efficient and Stable Perovskite Solar Cells

Abstract: The crystallinity of perovskite films is crucial for the performance and stability of perovskite solar cells (PSCs). Defects usually emerge in grain boundaries, leading to decomposition and non-radiative recombination of PSCs. Here, we present an effective additive engineering strategy to augment the long-term operation and stability of PSCs by doping a molecule with a symmetrical structure and bifunctional passivation, 2,5-thiophene dicarboxylic acid (TDCA), into the precursor solution. It is demonstrated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
(117 reference statements)
0
10
0
Order By: Relevance
“…The diffraction peaks located at 14°, 18°, and 28° corresponded to the (110), (210), and (220) planes of PVK, respectively. [ 41 ] The diffraction peak at 12.5° with a strong peak intensity should be assigned to PbI 2 , and these moderate residues of PbI 2 could passivate the surface defects of PVK films. [ 42 ] The increase in characteristic peaks intensity of the PVK proves that the modification of SPS is beneficial to improve the crystallinity of PVK films.…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peaks located at 14°, 18°, and 28° corresponded to the (110), (210), and (220) planes of PVK, respectively. [ 41 ] The diffraction peak at 12.5° with a strong peak intensity should be assigned to PbI 2 , and these moderate residues of PbI 2 could passivate the surface defects of PVK films. [ 42 ] The increase in characteristic peaks intensity of the PVK proves that the modification of SPS is beneficial to improve the crystallinity of PVK films.…”
Section: Resultsmentioning
confidence: 99%
“…[60] At the same time, the introduction of a water vapor barrier reduces the charge recombination loss between interfaces, improves the efficiency of carrier transmission, and improves the photovoltaic performance of the device. [53,61,62] XPS and UV-vis were used to study the elemental composition and chemical state of ALD SiAl x O y /SiO 2 . [63] We found that the optimized low-temperature ALD process did not cause any damage to the perovskite absorber layer.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that TDCA coordinates with the perovskite through hydrogen and PbÀO bonding, resulting in significantly enhanced crystallinity and defect passivation such as uncoordinated Pb 2+ and I À . [35] DOI: 10.1002/ente.202300907 All-inorganic CsPbI 2 Br perovskite solar cell shows superior thermal stability, but the power conversion efficiency falls behind organic devices, due to the existence of abundant defects. Halogen and metal ions at the grain boundaries induce the formation of defect states, which increases the probability of carrier recombination.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that TDCA coordinates with the perovskite through hydrogen and Pb−O bonding, resulting in significantly enhanced crystallinity and defect passivation such as uncoordinated Pb 2+ and I − . [ 35 ] Therefore, TDCA can effectively passivate the defects of perovskite. Regarding the passivation mechanism, it is still unclear.…”
Section: Introductionmentioning
confidence: 99%